Advances in health care management. Vol. 2 - Fottler, Myron D.; Savage, Grant T. 1954-; Blair, John D. 1944- (Advances in health care management., 2001)
The papers included in this volume may be categorized loosely into four general thematic sections: theoretical perspectives on the field of health care management; the role and impact of managed care; evolution of the health professions; enhancing health care organizational performance. The three papers in the first general section deal with a range of theoretical issues related to health care management, from complexity science to a theoretical comparison of integrated networks against systems, to how health care management researchers think about the research process. The three papers in the second section address the significant challenges faced by health care managers as they attempt to respond to the increasing impact of managed care. The third section's three papers look at the evolving roles of the health professions, including those of physicians as clinicians and as executives. The four papers in the final section focus on various approaches, from total quality management to use of work groups and transformational leadership, to enhancing health care organizational performance.